Video compression and encryption coding scheme based on zero tree - ZHANG Rong; ZHU Zhi-chao; YIN Dong; LIU Zheng-kai (Tongxin xuebao, 2007)
According to the security of the scalable video stream,an integrated video compression-encryption scheme was proposed.The scheme chooses wavelet transform as the compression platform,encrypts the zero-tree symbol during the zero-tree generation process to guarantee the security of the video.Furthermore,a multiple levels encryption was proposed to satisfy different consumers’ requirement.It is proved that the scheme kept the scalability of the encoding,has high security,and small impact on compression efficiency,so it is suitable for real-time video transferring on the network.